Effectiveness of internet-based self-help interventions for depression in adolescents and young adults: a systematic review and meta-analysis - Ma, Qian; Shi, Yimin; Zhao, Wei; Zhang, Huixiang; Tan, Dongmei; Ji, Congcong; Liu, Lin (BMC psychiatry, 2024)
To assess the effectiveness of Internet-based self-help interventions in treating depression in adolescents and young adults. A systematic search was conducted across six databases, including PubMed, to identify randomized controlled trials (RCTs) that satisfied the specified inclusion and exclusion criteria. The intervention measure consisted of Internet-based self-help interventions. A total of 23 randomized controlled trials (RCTs) were included in this analysis. Meta-analysis indicated that Internet-based self-help therapies significantly reduced depression scores in adolescents and young adults. (OR = -0.68, 95%CI [-0.88, -0.47], P < 0.001). We examined the effects of patient recruitment from various regions, medication usage, therapist involvement, weekly intervention time, and intervention duration. Patients selected from school, primary healthcare centers, clinics and local communities had better results. Intervention lasting 30 to 60 min and 60 to180 minutes per week were effective in the short term. The internet-based self-help intervention can be effective in treating depression in adolescents and young adults. However, factors such as patient recruitment locations, medication usage, Therapists' involvement, weekly intervention time, and intervention duration interacted with the outcome. Subgroup analysis on potential adverse effects and gender was impossible due to insufficient data from the included studies.